HANAFIY FIQHINING ILK NAZARIY ASOSLARI - Sobirjonova Zilola (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. Although the foundations of Sharia are based on the Qur’an and Sunna, it has undergone developmental stages like other legal systems. Various historical factors, including natural and climatic conditions, living standards, political and social structures, and the expansion of Islam into diverse cultural and ethnic regions, contributed to the evolution of Sharia. During the first three centuries, these influences shaped Islamic governance, institutions, and legal principles.